Transcriptome temporal and functional analysis of liver regeneration termination - Rychtrmoc, D; Hubálková, L; Víšková, A; Libra, A; Bunček, M; Červinková, Z (Physiological research, 2012)
Decades of liver regeneration studies still left the termination phase least elucidated. However regeneration ending mechanisms are clinicaly relevant. We aimed to analyse the timing and transcriptional control of the latest phase of liver regeneration, both controversial. Male Wistar rats were subjected to 2/3 partial hepatectomy with recovery lasting from 1 to 14 days. Time-series microarray data were assessed by innovative combination of hierarchical clustering and principal component analysis and validated by real-time RT-PCR. Hierarchical clustering and principal component analysis in agreement distinguished three temporal phases of liver regeneration. We found 359 genes specifically altered during late phase regeneration. Gene enrichment analysis and manual review of microarray data suggested five pathways worth further study: PPAR signalling pathway; lipid metabolism; complement, coagulation and fibrinolytic cascades; ECM remodelling and xenobiotic biotransformation. Microarray findings pertinent for termination phase were substantiated by real-time RT-PCR. In conclusion, transcriptional profiling mapped late phase of liver regeneration beyond 5(th) day of recovery and revealed 5 pathways specifically acting at this time. Inclusion of longer post-surgery intervals brought improved coverage of regeneration time dynamics and is advisable for further works. Investigation into the workings of suggested pathways might prove helpful in preventing and managing liver tumours.
Keywords: genetická transkripce; játra; metabolismus lipidů; Lipid Metabolism; regulace genové exprese; regenerace jater; Transcription, Genetic; Liver Diseases; Hepatectomy; krysa rodu Rattus; Peroxisome Proliferator-Activated Receptors; zvířata; potkani Wistar; hepatektomie; nemoci jater; Gene Expression Regulation; Liver; Liver Regeneration; Male; Rats, Wistar; transkriptom; Transcriptome; Rats; Animals; mužské pohlaví; Disease Models, Animal; receptory aktivované proliferátory peroxizomů; modely nemocí na zvířatech